CRITICAL ANALYSIS OF CROWDFUNDING TO FINANCE SMEs IN MUSLIM COUNTRIES - Sentot Imam Wahjono; Anna Marina; Mr Widayat (BALANCE: Economic, Business, Management and Accounting Journal, 2016)
ABSTRACT  The purpose of this paper is to critically analyze Crowdfunding as one of the alternative business funding, especially for Small and Medium-size Enterprises (SMEs) in the Muslim majority countries. This paper analyzes the current condition of the eightMuslim majority countries in the world:Egypt, Indonesia, Iran, Jordan, Malaysia, Pakistan, Saudi Arabia, and Turkey. The analysis was conducted in two aspects of readiness crowdfunding as SMEs financing in terms of entrepreneurial cultureand networked readiness. Analysis of an entrepreneurial culture based on the Global Report issued by the Global Entrepreneurship Monitor 2016, when an analysis of networked readiness is based on The Global Information Technology Report 2015 issued by the World Economic Forum. The preliminary findings of this paper indicate that crowdfunding can be implemented successfully nevertheless not ready to use crowdfunding as an alternative business financing, especially for SMEs.Keywords : Crowdfunding, alternative financing, Muslim countries, Entrepreneurial cultureCorrespondence to :1sentot.imamw@fe.um-surabaya.ac.id,2a_m_rina@yahoo.com, 3widayatumm@yahoo.com